2022
DOI: 10.3390/bioengineering9110607
|View full text |Cite
|
Sign up to set email alerts
|

Running Velocity and Longitudinal Bending Stiffness Influence the Asymmetry of Kinematic Variables of the Lower Limb Joints

Abstract: Running-related limb asymmetries suggest specific sports injuries and recovery circumstances. It is debatable if running speed affected asymmetry, and more research is required to determine how longitudinal bending stiffness (LBS) affected asymmetry. The purpose of this study was to investigate the influence of running velocity and LBS on kinematic characteristics of the hip, knee, ankle, metatarsophalangeal joint (MTP) and the corresponding asymmetry. Kinematic (200 Hz) running stance phase data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…However, other studies demonstrated two-to-three times larger deviations from symmetry (i.e., for peak force) during braking as opposed to push-off phases during the completion of repeated treadmill sprints [18,19] and for a range of low-to-high constant velocities [9]. The present study did not measure compensatory strategies at increasing belt speeds, which may have magnified some lower-limb kinematic variables while reducing others [13], potentially resulting in preserved SA scores for the analyzed gait variables. To further support our findings, additional studies examining joint kinematics and incorporating specific gait metrics, such as moments, angles, and velocities, are warranted.…”
Section: Asymmetry Is Metric-dependentcontrasting
confidence: 67%
See 1 more Smart Citation
“…However, other studies demonstrated two-to-three times larger deviations from symmetry (i.e., for peak force) during braking as opposed to push-off phases during the completion of repeated treadmill sprints [18,19] and for a range of low-to-high constant velocities [9]. The present study did not measure compensatory strategies at increasing belt speeds, which may have magnified some lower-limb kinematic variables while reducing others [13], potentially resulting in preserved SA scores for the analyzed gait variables. To further support our findings, additional studies examining joint kinematics and incorporating specific gait metrics, such as moments, angles, and velocities, are warranted.…”
Section: Asymmetry Is Metric-dependentcontrasting
confidence: 67%
“…However, some evidence shows that competitive runners exhibit more symmetrical running at fast velocities for certain mechanical parameters (e.g., flight time and mean vertical loading rate) but not for most of them [11]. A limitation of these studies is that they typically consider a narrow range of running velocities (e.g., 8-12 km•h −1 [12], 10-14 km•h −1 [13], or 11-14 km•h −1 [10]). By evaluating mechanical asymmetry across a wide spectrum of running velocities, we can gain further insight into how manipulating belt speed influences GRF asymmetry during treadmill runs.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetry coefficient (α) of left and right leg muscles at each weight-bearing step, which can reveal the asymmetry of left and right limb motor function [73].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, participants wore their own running shoes during testing, which could be confounding our results. Given that differences in footwear characteristics can underpin differences in running biomechanics [58][59][60][61][62], using a standardized shoe might have led to different study outcomes in terms of running biomechanics. Nonetheless, recreational runners are more comfortable wearing their own shoes [63], and show individual responses to novel footwear [63,64] and cushioning properties [65].…”
Section: Plos Onementioning
confidence: 99%